2022
DOI: 10.47577/tssj.v28i1.5822
|View full text |Cite
|
Sign up to set email alerts
|

The difficulty of making claims to knowledge in social science

Abstract: This paper considers three common types of claim to research knowledge, and the relative difficulty of making each type of claim in an empirically and logically justified manner. Before this, the paper looks at some more general issues often raised when discussing knowledge in social science, such as the nature of truth and justified belief, the existence of “isms” and paradigms treated like fashion accessories that one can adopt or not at will, and the intrinsic limitations of how we get to know about the “st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Perhaps most famously, Einstein (1920) produced theories of special and general relativity in physics which can demonstrate both the importance of observer standpoints, and how the phenomenon under investigation can be understood/resolved at a meta‐level for all standpoints. This is very different from something like relativism – which might assert that because there are many perspectives then all are inevitably equal, and anything can be or must be true (Gorard & Tan, 2022).…”
Section: The Need For Quality Judgementsmentioning
confidence: 94%
See 1 more Smart Citation
“…Perhaps most famously, Einstein (1920) produced theories of special and general relativity in physics which can demonstrate both the importance of observer standpoints, and how the phenomenon under investigation can be understood/resolved at a meta‐level for all standpoints. This is very different from something like relativism – which might assert that because there are many perspectives then all are inevitably equal, and anything can be or must be true (Gorard & Tan, 2022).…”
Section: The Need For Quality Judgementsmentioning
confidence: 94%
“…This review concerns the existing evidence on the use of financial intervention such as conditional cash transfers to help improve school attendance in developing countries, and comes from a larger project. In the report of that project, the weakest (0 rated) studies are simply ignored as they are judged not to contribute anything to knowledge (Gorard et al, 2022). The review studies are classified in terms of their quality (rows) and whether their results showed a benefit for attendance, no benefit or even harm, or a mixed set of results (columns).…”
Section: Cre Ating a Composite Judgementmentioning
confidence: 99%
“…My (descriptive) claim is that dominant views of trust grounded primarily in African scholarship can enhance our thinking about the specific problems black box clinical AI causes, at least from the African perspective. In this regard, the manuscript draws on an equally acceptable philosophical method to push the boundary of knowledge on the current discourse on the problems black box clinical AI creates within the clinical context (Gorard and Tan, 2022). This philosophical approach is not uncommon since this method has been adopted by different ethicists (Behrens, 2013;Cordeiro-Rodrigues and Ewuoso, 2022;Fayemi, 2018).…”
Section: Methodsmentioning
confidence: 99%